2020
DOI: 10.7250/itms-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments vs. TOPSIS to Select Hyperparameters of Neural Attention Models in Time Series Prediction

Abstract: Attention models are used in neural machine translation to overcome the challenges of classical encoder-decoder models. In the present research, design of experiments and TOPSIS methods are used to select hyperparameters of a neural attention model for time series prediction. The configurations selected by both methods are compared with out-of-sample data in time interval between January 2020 and April 2020 when global economies were significantly impacted due to Covid-19 pandemic. Results demonstrated that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The optimization of the properties of these materials can provide important information for the improvement of their mechanical properties for further applications. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is an appropriate method that has been widely applied for the optimization and prediction of various characteristics [49][50][51][52][53][54]. Some investigations on the nanocomposites of iron oxide nanoparticles with polymers have shown that these materials would be appropriate for the function improvement of electrical devices [55][56].…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of the properties of these materials can provide important information for the improvement of their mechanical properties for further applications. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is an appropriate method that has been widely applied for the optimization and prediction of various characteristics [49][50][51][52][53][54]. Some investigations on the nanocomposites of iron oxide nanoparticles with polymers have shown that these materials would be appropriate for the function improvement of electrical devices [55][56].…”
Section: Resultsmentioning
confidence: 99%